2016
DOI: 10.1080/17435390.2016.1189615
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of 40 nm diameter nanowires through the intestinal epithelium of Daphnia magna

Abstract: Nanowires (NWs) have unique electrical and optical properties of value for many applications including lighting, sensing, and energy harnessing. Consumer products containing NWs increase the risk of NWs being released in the environment, especially into aquatic ecosystems through sewage systems. Daphnia magna is a common, cosmopolitan freshwater organism sensitive to toxicity tests and represents a likely entry point for nanoparticles into food webs of aquatic ecosystems. Here we have evaluated the effect of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…GaInP nanowire segments have been shown to exhibit bright near infra-red photoluminescence with negligible bleaching and are therefore well-suited when stable emission is required during longitudinal measurements. [21][22][23] The fact that only the tip of the nanowire emits light allows for small variations in focus to occur without any loss of precision in the force estimation based on the localization of the nanowire tip.…”
Section: Development Of a Robust Methods For Global Force Readout At Hmentioning
confidence: 99%
“…GaInP nanowire segments have been shown to exhibit bright near infra-red photoluminescence with negligible bleaching and are therefore well-suited when stable emission is required during longitudinal measurements. [21][22][23] The fact that only the tip of the nanowire emits light allows for small variations in focus to occur without any loss of precision in the force estimation based on the localization of the nanowire tip.…”
Section: Development Of a Robust Methods For Global Force Readout At Hmentioning
confidence: 99%
“…[55] A recent study illustrated that a high degree of fragments was observed for GaP/GaInP nano wires after ingestion by the Daphnia, which facilitated the trans location of NMs across the intestinal epithelium. [56] Another case is that the addition of intestinal simulated fluid changed the size and aggregation state of polyvinylpyrrolidone (PVP) coated Ag NMs and increased the cellular uptake and toxicity of NMs on Caco2 cells. [52] The reason for this phenomenon might be that the release of silver ion mediated by intestinal fluid is involved in the generation of hydroxyl radical.…”
Section: Nano-iec Interaction and Subsequent Biological Effectsmentioning
confidence: 99%
“…It is also of importance to understand the aggregation properties of nanoparticles in an aqueous environment, as well as how they are affected by the digestive system of the organisms. Nanomaterials have been detected inside Daphnia after incubation (Scanlan et al 2013;Mattsson et al 2016) possibly by being passively transported through the feeding current of the animal. Changes in particle aggregation state in the surrounding medium are likely to affect the filtration and uptake of nanoparticles by Daphnia.…”
Section: Introductionmentioning
confidence: 99%